Decision Support Conceptual Framework for Zoonosis Emerging System - Adhistya, Erna; Dayang R.A. Rambli, Rohaya; Dominic P, Dhanapal Durai (2010)
Abstract— Emerging zoonosis represents an increasing threat to animal and human health. Zoonosis is any infectious disease that is able to be transmitted from other animals, both wild and domestic, to humans. The increasing number of zoonotic diseases coupled with the frequency of occurrences, especially lately, has made the need to study and understand theses diseases a major concern among researchers from various disciplines. It is important to have a single system that is able to analyze the relationship between different diseases in emergence zoonosis. However, the development of such system presents a daunting and yet to be explored task. Many factors have been attributed but inadequate information has been identified as a major challenge. In this paper, a review on zoonosis aspects and previous research on zoonosis are presented. Based on this review, a framework for developing an emerging zoonosis system is proposed. Therefore, the initial findings of framework were also presented. The system is considered as a zoonosis risk-emergence based on similar pattern recognition of zoonosis domain across different zoonotic diseases. Potential challenges in developing an emerging zoonosis model based on quantitative approach to unify zoonosis knowledge from different diseases into a single system were highlighted.